Whispers from vestigial nubbins: Arrested development provokes trait loss in toads. Issue 1 (27th October 2020) - Stynoski, Jennifer L.; Womack, Molly C.; Trama, Florencia A.; Coloma, Luis A.; Hoke, Kim L.
Abstract: Despite the use of acoustic communication, many species of toads (family Bufonidae) have lost parts of the tympanic middle ear, representing at least 12 independent evolutionary occurrences of trait loss. The comparative development of the tympanic middle ear in toads is poorly understood. Here, we compared middle ear development among two pairs of closely related toad species in the genera Atelopus and Rhinella that have (eared) or lack (earless) middle ear structures. We bred toads in Peru and Ecuador, preserved developmental series from tadpoles to juveniles, and examined ontogenetic timing and volume of the otic capsule, oval window, operculum, opercularis muscle, columella (stapes), and extracolumella in three‐dimensional histological reconstructions. All species had similar ontogenesis of the otic capsule, oval window, operculum, and opercularis muscle. Moreover, cell clusters of primordial columella in the oval window appeared just before metamorphosis in both eared and earless lineages. However, in earless lineages, the cell clusters either remained as small nubbins or cell buds in the location of the columella footplate within the oval window or disappeared by juvenile and adult stages. Thus, columella growth began around metamorphosis in all species but was truncated and/or degenerated after metamorphosis in earless species, leaving earless adults with morphology typical of metamorphic anurans. Shifts in the timing or expression of biochemical pathways that regulate the extension or differentiation of the columella after metamorphosis may be the developmental mechanism underlying convergent trait loss among toad lineages. Abstract : Highlights: Tympanic middle ear development begins at a similar time in eared and earless toad species but is truncated in earless species around metamorphosis. This proximate mechanism could underlie repeated ear losses in the clade.